EFEKTIVITAS DIRECT MARKETING DAN VOUCHER DISKON MELALUI LIVE STREAMING DALAM MENINGKATKAN REPURCHASE INTENTION PADA SHOPEE: (STUDI KASUS KONSUMEN SHOPEE KATEGORI FASHION DI KOTA DEPOK) - Adzra Kamilah, Hana; Purwinarti, Titik; Wartiningsih, Endah (Jurusan Administrasi Niaga Politeknik Negeri Jakarta, 2025)
This research aims to determine and analyze the effectiveness of direct marketing and discount vouchers through live streaming in increasing repurchase intention on Shopee (a case study on Shopee consumers in the fashion category in Depok City). This research uses a qualitative approach with a descriptive method. Primary data is collected using observation, direct interviews with relevant informants, and documentation. Secondary data collection is divided into two, namely internal data and external data. The data processing used in this research is source triangulation with data analysis techniques starting from data reduction, data display, and conclusion drawing or verification. Effectiveness measurements include understanding, targeting accuracy, timeliness, goal achievement, and tangible changes. The research results show that direct marketing and discount vouchers have achieved effectiveness in increasing repurchase intention. This is evidenced by data obtained directly from consumers as informants that there has been a change in the number of transactions before and after the launch of the live- streaming feature. The results of the analysis of the effectiveness of direct marketing and discount vouchers in increasing repurchase intention on Shopee have met the effectiveness measurements, namely understanding, targeting accuracy, timeliness, goal achievement, and tangible changes.